Persistent Left Superior Vena Cava: A Rare Association - Jayalaxmi Shripati Aihole MCH (SAGE Publishing, 2021)
Persistent left superior vena cava (PLSVC) is the most frequent abnormality in the general population with the frequency of 0.1% to 0.5%. It results from the failure of the involution of the left anterior cardinal vein. Right and Left SVC can coexist together in 80% to 90% of cases. Association of PLSVC with ano rectal malformation (ARM) is very rarely reported. Hence, here is a report of a unique case of PLSVC in a female neonate with ARM